PERCEPTION OF ACCOUNTING STUDENTS REGARDING COMPLIANCE WITH ACCOUNTING RULES, UNETHICAL BEHAVIOR, AND INDIVIDUAL MORALITY AGAINST ACCOUNTING FRAUD WITH INTERNAL CONTROL AS MODERATION - Rahayu , Ruci Arizanda; Pradasiwi, Arda Walika; Nirwana, Nihlatul Qudus Sukma; Ernandi, Herman (International Journal of Business, Law and Political Science, 2025)
Objective: This research aims to examine accounting students' perceptions of the influence of compliance with accounting rules, unethical behavior, and individual morality on accounting fraud with internal control as a moderator. Method: This study uses a quantitative approach. The population is active undergraduate (S-1) students in the accounting study program class of 2019, 2020 and 2021, Faculty of Business, Law and Social Sciences, Muhammadiyah University of Sidoarjo. Data analysis techniques were carried out using SmartPLS version 3.0. Result: The results of this research indicate that 1) Compliance with accounting rules has no effect on accounting fraud. 2) Unethical behavior influences accounting fraud. 3) Individual morality has a significant effect on accounting fraud. 4) Internal control moderates compliance with accounting rules against accounting fraud. 5) Internal control moderates unethical behavior towards accounting fraud. 6) Internal control cannot moderate individual morality towards accounting fraud. Novelty: As a dynamic that often occurs, accounting fraud is a problem that attracts world attention, and various issues related to accounting fraud have received a lot of attention, especially from researchers who are trying to reveal how and why accounting fraud can occur.